ANALISIS TINGKAT KEMISKINAN PRODUSEN KOPRA DI DESA TOLONGANO KECAMATAN BANAWA SELATAN KABUPATEN DONGGALA - Lien Damayanti (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
This research aims to know if the earns of copra producer can fulfill tha need of their family and relatives, and also to know if all copra producer in tolongano village stay under or above line of  poverty level, if we assume that their earns take from copra processing bussines only.  This research was aabout study case at copra producer ini tolongano village.  It was coundected from October to December 2006 in Tolongano Village south Banawa Sub District Donggala District.  The result shown that average earn of copra producer was about Rp. 332,173 per period, with the average of family members was about 5 people.  Therefore, if we make a conversion based on rice equal need, it can be concluded that it was 88,58 kg/person/year.  In conclusion, if copra producer only earn from copra processing bussines, overall copra producer categorized with “very poor”.